2006
DOI: 10.1111/j.1399-0004.2006.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

The personal experience of juvenile Huntington's disease: an interpretative phenomenological analysis of parents' accounts of the primary features of a rare genetic condition

Abstract: There has been a paucity of research into the psychosocial impact of juvenile Huntington's disease (JHD) on the child and the family. The study reported here is part of larger project that aimed to address this and investigate the social and health care needs of those affected by JHD. Ten semistructured interviews with the main caregiver(s) were carried out and were analyzed using the qualitative methodology interpretative phenomenological analysis. The main themes arising from the analysis are reported here: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Qualitative methods are valuable when attempting to understand the participant’s perspective, especially when the phenomenon is rare. A British study employed such an approach to examine the experience of parents/primary carers of children with JHD [64]. …”
Section: Views Of Familiesmentioning
confidence: 99%
“…Qualitative methods are valuable when attempting to understand the participant’s perspective, especially when the phenomenon is rare. A British study employed such an approach to examine the experience of parents/primary carers of children with JHD [64]. …”
Section: Views Of Familiesmentioning
confidence: 99%
“…Key findings included: how families experienced isolation and a lack of understanding about JHD; how many parents were aware that something was wrong with their child; and perceptions of helpful and unhelpful forms of social support from families, friends and health-care professionals. [11][12][13] The study reported here aims to develop and extend the existing understanding of the personal experience of families living with a child with JHD; how they think, feel and manage the challenges that face them. The study recruited parents from four European countries: Italy, The Netherlands, Poland and Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…IPA has been employed in a number of studies examining psychosocial issues in genetics (see, eg, references [15][16][17] in addition to the previous work on JHD. [11][12][13] …”
Section: Introductionmentioning
confidence: 99%
“…It should therefore not simply be viewed as an approach to data analysis. Although deemed to be a ‘young’ approach to qualitative research (Larkin, Watts, and Clifton, , 105), IPA is informed by hermeneutics, phenomenology and ideography (Smith, Eatough, Stanley, et al., ), identifying that the methodology has well‐grounded theoretical underpinnings. The study reported in this article was approached via IPA, as this perspective is particularly relevant when investigating significant experiences in participants’ lives (Smith, Eatough, Stanley, et al., ).…”
Section: Methodsmentioning
confidence: 99%